Exogenous Bacillus subtilis can reduce the damage caused by waste drilling fluid to ryegrass (Lolium perenne) - Lu Yang; Yuandong Zhu; Heng Zhao; Xiaohu Chen; Zihan Cheng; Yongjun Fei (Plant Stress)
Oil and gas drilling waste fluid are an alkaline mixture with complex composition that can be hazardous to plants if leakage occurs during transportation and disposal. Bacillus subtilis is well-known for its adaptable to adversity and its beneficial effect on plants and soil. In this study, the novel ultra-slippery water-based drilling fluids were evaluated as potentially hazardous liquids capable of inhibiting ryegrass (Lolium perenne) germination and growth. However, the combination of ryegrass and B. subtilis successfully decreased the negative effects of waste drilling fluid stress, while increasing the levels of antioxidant enzymes and osmotic regulatory substances, resulting in improved ryegrass germination and growth. Furthermore, B. subtilis enhanced the activation of nitrogen, phosphorus, and potassium in the soil, which improved soil conditions and promoted ryegrass development. This study proposes a novel approach for combined remediation of waste drilling fluid pollution in oil and gas drilling sites using microbial agents and plants, while also furnishing resources for enhancing ryegrass resilience and facilitating ecological restoration.